The effectiveness of an internet-based support program on maternal self-efficacy, postpartum depression and social support for primiparous women during the COVID-19 pandemic: Randomized controlled trial - Zhang, Yuting; Zhu, Jiemin; Li, Sen; Huang, Lingling; Fang, Qiyu; Zheng, Xujuan (Frontiers in Public Health, 2023)
Background: Many primiparous women usually encounter various parenting and mental health issues after childbirth. The effects of intervention based on internet platform on parenting and mental health outcomes for Chinese first-time mothers remain unknown during the COVID-19 pandemic. Therefore, our research aimed to evaluate the effectiveness of an internet-based support program (ISP) on parenting and mental health outcomes for primiparous women amid the pandemic. Methods: A multicenter randomized controlled trial was conducted. From May 2020 to March 2021, 242 primiparous women were recruited in the maternity wards of two hospitals in China. Women in control group (n=118) received the routine postpartum care, and women in intervention group (n=118) accessed to the ISP intervention and routine postpartum care. Intervention outcomes were measured at baseline before randomization (T0), post-intervention (T1), and three-month follow up (T2) through questionnaires. Results: In comparison with women in the control group, women in the intervention group had a significantly higher score of maternal self-efficacy (MSE); and a lower score of postpartum depression (PPD) at T1 and T2; and a higher score of social support at T1, but no significant difference at T2. Conclusions: The effect of ISP was evaluated to significantly increase the levels of MSE, social support, and to alleviate PPD symptoms for Chinese first-time mothers. As an effective and easily accessible intervention, ISP could become a significant source for health professionals to support primiparous women on parenting and mental health during the COVID-19 pandemic.